The Role of Design, Construction, and Real Estate in Advancing the Sustainable Development Goals - Walker, Thomas; Cucuzzella, Carmela; Goubran, Sherif; Geith, Rana (Sustainable Development Goals Series, 2023)
XXIX, 243 p. 59 illus., 32 illus. in color.